2016
DOI: 10.1111/nyas.13284
|View full text |Cite
|
Sign up to set email alerts
|

Quality of governance and effectiveness of protected areas: crucial concepts for conservation planning

Abstract: Protected areas (PAs) are a key tool for biodiversity conservation and play a central role in the Convention on Biological Diversity. Recently, the effectiveness of PAs has been questioned, and assessing how effective they are in enabling the future persistence of biodiversity is not trivial. Here, we focus on terrestrial PAs and clarify the terminology related to PA effectiveness, distinguishing between management and ecological aspects. We suggest that the quality of governance affects both aspects of effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 76 publications
(209 reference statements)
2
70
0
8
Order By: Relevance
“…Management effectiveness research aims to improve the way PAs are managed by investigating the relationship between management actions and ecosystem condition (Timko & Innes, 2009). Most of these standardized tools often lack an assessment of the state of biodiversity or ecosystems (Coad et al, 2015), limiting analysis of how management relates to PA outcomes (Carranza, Manica, Kapos, & Balmford, 2014;Eklund & Cabeza, 2017;Nolte & Agrawal, 2013). Most of these standardized tools often lack an assessment of the state of biodiversity or ecosystems (Coad et al, 2015), limiting analysis of how management relates to PA outcomes (Carranza, Manica, Kapos, & Balmford, 2014;Eklund & Cabeza, 2017;Nolte & Agrawal, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Management effectiveness research aims to improve the way PAs are managed by investigating the relationship between management actions and ecosystem condition (Timko & Innes, 2009). Most of these standardized tools often lack an assessment of the state of biodiversity or ecosystems (Coad et al, 2015), limiting analysis of how management relates to PA outcomes (Carranza, Manica, Kapos, & Balmford, 2014;Eklund & Cabeza, 2017;Nolte & Agrawal, 2013). Most of these standardized tools often lack an assessment of the state of biodiversity or ecosystems (Coad et al, 2015), limiting analysis of how management relates to PA outcomes (Carranza, Manica, Kapos, & Balmford, 2014;Eklund & Cabeza, 2017;Nolte & Agrawal, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the findings presented in this paper, we question whether areas such as those studied here, which have retained biological values for so long but are currently facing challenges, could be considered as 'potential OECMs' only if their conservation values are properly assessed. Similar concepts of conditionality and governance are being discussed at large in the context of protected areas (Eklund & Cabeza, 2016). While substantial progress has been made in operationalising clear indicators of protected area effectiveness (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This means that even if a PA currently has little impact, due to location (see previous section), but sound management is in place, it might start having an impact once the pressures increase. This links to the wider debate of proactive versus reactive approaches to conservation (Brooks et al, 2006;Eklund & Cabeza, 2017), and how different data on PA effectiveness could be used to prioritize actions, which we discuss next. An inspection of the changes in the land cover data showed that this was the result of relocated pressures, spreading to previously remote regions once the more accessible land had already lost its forest cover.…”
Section: Dynamic Pressures Make Static Comparison Between Managemenmentioning
confidence: 98%
“…Finally, the PAME data ignores aspects related to the wider quality of governance, such as for example law enforcement and corruption (Eklund & Cabeza, 2017). Previous studies have shown that PA managers often report such issues as being main obstacles for carrying out effective management (Pyhälä et al, 2019;Schleicher et al, 2019), as the mandate of a local manager is quite limited in the face of such powerful drivers.…”
Section: Caveatsmentioning
confidence: 99%
See 1 more Smart Citation